Motivasi Orang Tua Santri dalam Menyekolahkan Anaknya di Pesantren Darul Muta’allimin Pasca Meninggalnya Abuya Syekh H. Bahauddin Tawar - Baharuddin Bancin; Mukhsin Nyak Umar; Masbur Masbur (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2023)
This study aims to determine the role of parents of students in sending their children to the Darul Muta'allimin Islamic Boarding School. And to describe the level of motivation of parents in sending their children to the Darul Muta'allimin Tanah Merah Islamic Boarding School after the death of Abuya Syekh H. Bahauddin Tawar. This study used a qualitative approach with data collection techniques through observation, interviews and documentation. The results of the study show that: 1) The role of parents in sending their children to the Darul Muta'allimin Islamic Boarding School is divided into 3 roles, namely Providing Support, Providing Motivation and Supervising. 2) The level of parents' motivation was very high in sending their children to the Darul Muta'allimin Tanah Merah Islamic Boarding School after the death of the late Alm. Abuya H. Bahauddin Tawar. This can be seen from the increasing number of students every year. In the 2022/2023 academic year, the total number of students at the Darul Muta'allimin Islamic Boarding School was recorded at 1,414 students.